Malawi can end hunger after the 2025 elections if bold steps are taken to transform food systems - De Weerdt, Joachim; Chirwa, Gowokani Chijere; Duchoslav, Jan; Nagoli, Joseph; Cockx, Lara (The Conversation, 2025)
Malawi has a history of peaceful democratic transitions. Since the advent of multiparty politics in 1994, power has regularly shifted between rival parties. Citizens and institutions have upheld electoral democratic norms, from respecting term limits to rerunning elections after irregularities.